Risking lives for living: a study on underwater fishing in the Padma River, Bangladesh - Parvez, Md. Taskin; Chaki, Nipa; Mohsin, ABM; Galib, Shams M. (Journal of Fisheries, 2017)
Different types of fishing methods and gears are being employed across the globe including Bangladesh. This study describes the underwater fishing method in the Padma River- one of the three largest rivers in Bangladesh. Standardised efforts have been made for collecting data of interest between September 2016 and May 2017. Two types of underwater fishing, with or without using oxygen cylinders, were recorded. Mean duration of fishing per effort was higher (by 382%) when fishermen used oxygen cylinders. Mean water depth of fishing sites was also higher when oxygen cylinders were used. Three species of finfish (Rita rita, Sperata seenghala and Labeo calbasu) and one freshwater prawn species (Macrobrachium dayanum) have been identified in the catch. The catch was dominated by M. dayanum in both fishing types (27 ± 9.3 [with oxygen] and 15 ± 5.2 [without oxygen]). However, all the number of caught fish species varied significantly among different sampling months in both fishing methods (P < 0.001) except L. calbasu in fishing with oxygen cylinder. A number of health issues of the fishermen were also recorded.